Influence of hypoxia training on the aerobic capacity of an elite race walker - Maciejczyk, M.; Sudol, G.; Szygula, Z. (Human Movement, 2012)
The aim of the study was to evaluate the influence of a combination of two different hypoxic training models ("live high-train high" and "live high-train low" with the use of a hypoxic tent) on the aerobic capacity of a elite race walker preparing for the 2009 IAAF World Championships. Methods. Evaluation of VO2max and the second ventilatory threshold was performed three times: 1) after four weeks training without hypoxic conditions, 2) after 28 days training in normoxia and sleeping for 8 h/day in a hypoxic tent (normobaric hypoxia, simulated hypoxia at 2133 m above sea level) and 3) after 26 days of classical altitude training at a moderate altitude of about 1800 m ASL (hypobaric hypoxia). The hematological parameters of the athlete`s blood (hematocrit, hemoglobin concentration, and erythrocytes and reticulocytes counts) were also measured after each stage. Results. After training in normoxia and sleeping in a hypoxic tent the ventilatory threshold was noted at a higher work intensity and featured an improvement in his hematological parameters, although VO2max was unchanged (compared to training without hypoxia). After classical altitude training a higher level of VO2max was observed (with a ventilatory threshold level similar to the level after training in normobaric hypoxia), but the hematological indices were lower than the levels observed before starting hypoxic training. Conclusions. The combination of two methods of hypoxic training improved the aerobic capacity of the test subject, but an improvement in the analyzed hematological indicators was observed only after LH + TL training. After training in LH + TH these indicators were lower in comparison to the levels prior hypoxic training. The changes in the hematological indices after hypoxic training did not seem to have a significant influence on aerobic capacity; the observed improvements in physical performance may result from other factors.